2002
DOI: 10.1017/s0022112002008054
|View full text |Cite
|
Sign up to set email alerts
|

On the frequency selection of finite-amplitude vortex shedding in the cylinder wake

Abstract: In this paper it is shown that the two-dimensional time-periodic vortex shedding régime observed in the cylinder wake at moderate Reynolds numbers may be interpreted as a nonlinear global structure and its naturally selected frequency obtained in the framework of hydrodynamic stability theory. The frequency selection criterion is based on the local absolute frequency curve derived from the unperturbed basic flow fields under the assumption of slow streamwise variations. Although the latter assumption is only a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

29
179
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 176 publications
(209 citation statements)
references
References 33 publications
29
179
1
Order By: Relevance
“…The asymmetry in the vortex street pattern is characteristic of the frontal regime and does not occur in the quasigeostrophic regime where both cyclones and anticyclones have about the same size and shape even when the base velocity profile is asymmetric. Note that for the incompressible 2D wake 25 or for the present quasigeostrophic wake, since the perturbations are selfsustained due to the presence of an absolutely unstable region downstream of the cylinder, a local temporal analysis predicts an estimate of the Strouhal number three to four times too large. Hence, this strongly suggests a change in the nature of the wake instability when the geopotential fluctuations become large enough.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…The asymmetry in the vortex street pattern is characteristic of the frontal regime and does not occur in the quasigeostrophic regime where both cyclones and anticyclones have about the same size and shape even when the base velocity profile is asymmetric. Note that for the incompressible 2D wake 25 or for the present quasigeostrophic wake, since the perturbations are selfsustained due to the presence of an absolutely unstable region downstream of the cylinder, a local temporal analysis predicts an estimate of the Strouhal number three to four times too large. Hence, this strongly suggests a change in the nature of the wake instability when the geopotential fluctuations become large enough.…”
Section: Discussionmentioning
confidence: 76%
“…In that incompressible case, Pier 25 showed that the wake flow is locally convectively unstable just behind the cylinder. This convectively unstable zone ends in the streamwise direction at x = 0.2D approximately while further down an absolutely unstable zone is present.…”
Section: Absolute/convective Instabilitymentioning
confidence: 99%
“…Barkley (2006) reports that a linear global stability analysis can still satisfactorily predict the shedding frequency well above the instability threshold provided it is performed on the time-averaged mean flow, not the base flow. This is somehow reminiscent of Hammond & Redekopp (1997) and Pier (2002), who early noticed that a linear criterion applied to the mean flow was remarkably successful in predicting the frequency of the unsteadiness in the frame of local stability analyses. In addition, Barkley (2006) shows that the mean flow is almost neutrally stable.…”
Section: Introductionmentioning
confidence: 83%
“…The success of this semi-empirical approach was demonstrated by various investigations, revealing that linear stability analysis is a powerful tool to model large-scale coherent structures in turbulent flows. Accordingly, this method can be applied at different degrees of complexity and accuracy, ranging from local stability analysis (Gaster et al 1985;Cohen & Wygnanski 1987a;Pier 2002;Juniper, Tammisola & Lundell 2011;Oberleithner et al 2011) through parabolized stability analysis (Herbert 1997;Gudmundsson & Colonius 2011) to global stability analysis (Barkley 2006;Meliga, Pujals & Éric 2012).…”
Section: Theoretical Conceptmentioning
confidence: 99%